Analysis of the effects of the transitional period on performance parameters in young soccer players - Villanueva-Guerrero, O.; Mainer-Pardos, E.; Nobari, H.; Lozano, D.; Arjol-Serrano, J. -L.; Roso-Moliner, A. (Acta Kinesiologica, 2023)
Purpose: The transition period has been shown to produce detraining effects in soccer players and could increase the risk of injury. The main purpose of this study was to analyse the effects of the transition period on lower body power levels through the vertical and horizontal jump in young players and compare them with the first part of the regular season, using the peak height velocity (PHV) as a covariate.